New Directions in Development Economics - Lundahl, Mats; Ndulu, Benno (Routledge Studies in Development Economics, 2003)
New Directions in Development Economics is divided into two parts. The first half considers the dilemna of growth with special reference to its environmental cost. The second half focuses on the role of the state in the context of the growing dominance of the free market argument. The contributors include Paul Collier, Partha Dasgupta, Ronald Findlay and Deepak Lal.